Evaluation of Waste Management for Ecotourism Development: A Case Study of Goa Rangko, Labuan Bajo, West Manggarai Regency, East Nusa Tenggara, Indonesia - I Wayan Koko Suryawan; Rachmat Mulyana; Imelda Masni Juniaty Sianipar; Mega Mutiara Sari; Wisnu Prayogo; Aarce Tehupeiory (Universitas Diponegoro, 2023)
The development of ecotourism in Goa Rangko, Labuan Bajo, West Manggarai Regency, East Nusa Tenggara, has increased waste generation, resulting in environmental degradation and negative impacts on the tourism industry. To address this issue and achieve sustainable tourism, this study aims to investigate the current waste management system in Goa Rangko and propose an optimized solution. The research was conducted through direct field observations and the collection of secondary data from literature and government documents. Waste characterization studies were undertaken to determine waste generation and composition. Based on the findings, a Material Recovery Facility (MRF) was recommended for waste management. The MRF would encompass a source-to-final processing system, ensuring efficient waste handling. Any residue from the process would be appropriately disposed of in the landfill. In addition to the MRF, the study proposes the involvement of the local community, along with education and awareness-raising programs. These initiatives aim to foster a sense of responsibility among the residents and tourists in managing waste sustainably. Moreover, the study suggests implementing an ecotourism certification program to support sustainable tourism development in Goa Rangko.